2004
DOI: 10.1021/bp0342304
|View full text |Cite
|
Sign up to set email alerts
|

Population Balance Approach to Modeling Hairy Root Growth

Abstract: Though numerous models have been developed to describe the growth of microbial cell cultures, far fewer models are available to describe the growth of hairy root cultures. Here a population balance model is proposed to simulate the growth of hairy roots. The model accounts for the increase in biomass due to elongation of a branch by cell division as well as the formation of new branches. The model incorporates the fact that although the likelihood of the formation of a new lateral branch is a maximum at a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Cell size did not correlate in our study with the rate of root elongation. This may be due to the in vitro effect on the propagation of root segments, rather than whole plants (Han et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cell size did not correlate in our study with the rate of root elongation. This may be due to the in vitro effect on the propagation of root segments, rather than whole plants (Han et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have revealed that oxidative burst, NO (nitric oxide) generation, RGD (Arg-Gly-Asp)-binding proteins, mitogen-activated protein kinase-like cascades and phospholipid signalling play important roles in the response of Taxus (yew) cells to shear stress [6][7][8][9][10][11][12]. These events were all closely related to the properties of cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the tissue growth by measuring osmolality (concentrations of different components) and the conductivity of the medium during culture are the examples of mathematical estimation of root growth through fresh weight time course data (Leduc et al 2006;Cloutier et al 2008). Another relevant example that uses the mathematical calculation to study the biomass increment based on population balance approach has also been proposed (Han et al 2004). Such examples of inclusion of interdisciplinary approach would definitely provide new dynamism and dimensions to the HRBP.…”
Section: Growth Simulations and Modelingmentioning
confidence: 99%